2020
DOI: 10.1038/s41467-020-16945-8
|View full text |Cite
|
Sign up to set email alerts
|

Elastomeric polyamide biomaterials with stereochemically tuneable mechanical properties and shape memory

Abstract: Biocompatible polymers are widely used in tissue engineering and biomedical device applications. However, few biomaterials are suitable for use as long-term implants and these examples usually possess limited property scope, can be difficult to process, and are nonresponsive to external stimuli. Here, we report a class of easily processable polyamides with stereocontrolled mechanical properties and high-fidelity shape memory behaviour. We synthesise these materials using the efficient nucleophilic thiol-yne re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 78 publications
(75 reference statements)
2
55
0
Order By: Relevance
“…This behavior is consistent with a more elastic material that is expected from the interruption of crystallinity through the introduction of ester groups into the main chain that disrupt chain packing and increase chain mobility. These findings were confirmed via differential scanning calorimetry (DSC) which showed that increasing % cis without altered succinate content increased the glass transition temperature in line with results from our previous work 5 , 29 . Significantly, the materials exhibit high thermal stability and the onset of degradation temperatures exceeds 350 °C.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…This behavior is consistent with a more elastic material that is expected from the interruption of crystallinity through the introduction of ester groups into the main chain that disrupt chain packing and increase chain mobility. These findings were confirmed via differential scanning calorimetry (DSC) which showed that increasing % cis without altered succinate content increased the glass transition temperature in line with results from our previous work 5 , 29 . Significantly, the materials exhibit high thermal stability and the onset of degradation temperatures exceeds 350 °C.…”
Section: Introductionsupporting
confidence: 89%
“…Until now, no synthetic resorbable elastomer or elastomer-like polymer system have afforded independent control of mechanical properties and degradation de novo 2 . We recently reported the first metal-free, stereocontrolled step-growth polymerization via a nucleophilic thiol-yne addition which yielded a series of thermally-processable elastomers in which the mechanical properties were controlled by the double bond stereochemistry 5 , 29 . The double bond stereochemistry (% cis ) in each thiol-yne step growth polymer was tuned based on solvent polarity and organic base which is able to preferentially direct the thiol addition to the cis stereochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastomeric materials have also been utilized in biomedical applications such as biomaterial design and tissue engineering. Worch et al 202 have developed a biocompatible elastomeric polyamide with shape memory properties to be used in long‐term implants. They have also studied high trans samples with 67% trans and high cis samples with 86% cis for their hydrolytic stability and water uptake behaviors in relation to biocompatibility and shape memory properties.…”
Section: Applications Of Smesmentioning
confidence: 99%
“…Shape memory polymers (SMPs), a kind of burgeoning smart materials, have captured extensive attention in the biomedical field [ [17] , [18] , [19] , [20] , [21] ]. SMPs have the ability to switch its shape between a programmed and an initial state under various stimuli such as heat [ 22 , 23 ], light [ 24 , 25 ], water [ 26 , 27 ], or magnetism [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%